KONSENTRASI LETAL EKSTRAK DAUN PRONOJIWO (Euchresta horsfieldii) TERHADAP TIGA SERANGGA HAMA PADI WERENG COKLAT (Nilaparvata lugens), WALANG SANGIT (Leptocorisa acuta) DAN PENGGEREK BATANG (Tryporiza innotata) - Hoiri Hoiri; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2013)
The aims of this study to test the killing effect of aqueous extract of leaf pronojiwo (E. horsfieldii) on mortality of rice pests N. lugens, L. acuta and rice T. innotata. Study was conducted in a completely randomized exprimental design with 5 level of water extract of E. horsfieldii (0, 40, 50, 66,67, and 100 g/l in water), each of treatment was 5 replication. Application have done by spraying water extract of leaves Pronojiwo to 3 types of rice pest insects reared in containment measures 80 x 25 cm2, for each lid containing 10 head insects. Observations of rice pests mortality for 24 hours after application of aqueous extract E. horsfieldii. The results of this study showed the aqueous extract of E. horsfieldii have significant effect (P <0.05) on mortality of rice pests. Aqueous extract of leaves E. horsfieldii can kill pests of rice N.lugens, L. acuta, and T. innotata with lethal concentration 50 (LC50) of 4.46, 4.48 and 4.49 g/l water. Key words : E. horsfieldii, mortality, N.lugens, L. acuta, and T. innotata